2019
DOI: 10.1039/c8nj05399e
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance asymmetric supercapacitor based on Ni3S2-coated NiSe arrays as positive electrode

Abstract: Cotton-like Ni3S2-coated NiSe rod composite electrode was synthesized by cyclic voltammetry electrodeposition with satisfactory electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…where, I, ∫ 𝑉𝑑𝑡, m, and t are the discharge current (mA), integral area under the discharge curve, masses, and discharging time (s), respectively. The results are comparable or even superior to those of previously reported supercapacitors (Table 2), such as the rGO@Ni3S2//AC (37.19 W h kg −1 at 399.9 W kg −1 ), Ni3S2//AC (36 W h kg −1 at 400 W kg −1 ), and Ni3S2@CoS//AC (23.69 W h kg −1 at 268.95 W kg −1 ) devices [66,[79][80][81][82][83][84][85]. A comparison of these results based on power and energy densities with related reported devices is also summarized.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…where, I, ∫ 𝑉𝑑𝑡, m, and t are the discharge current (mA), integral area under the discharge curve, masses, and discharging time (s), respectively. The results are comparable or even superior to those of previously reported supercapacitors (Table 2), such as the rGO@Ni3S2//AC (37.19 W h kg −1 at 399.9 W kg −1 ), Ni3S2//AC (36 W h kg −1 at 400 W kg −1 ), and Ni3S2@CoS//AC (23.69 W h kg −1 at 268.95 W kg −1 ) devices [66,[79][80][81][82][83][84][85]. A comparison of these results based on power and energy densities with related reported devices is also summarized.…”
Section: Resultssupporting
confidence: 82%
“…Comparison of the electrochemical energy storage performance observed in this study with those of previously reported asymmetric devices based on Ni 3 S 2 and AC electrodes[66,[79][80][81][82][83][84][85].…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…The characteristic peaks at 855.6 eV of Ni 2p 3/2 and 873.3 eV of Ni 2p 1/2 in the Ni 2p XPS spectrum demonstrated the two spin-orbit pairs of Ni 2+ (Figure 1g) and the peaks at 54.6 eV of Se 3d 5/2 and 55.4 eV of Se 3d 3/2 in the Se3d spectrum represented the characteristic peaks of Se 2-(Figure 1h), and all of above results indicated the successful formation of NiSe NPs. [41] The poorly resolved X-ray diffraction peaks suggested their weak crystallinity (Figure 1i). [42] Thermo gravimetric analysis (TGA) results showed the amount of PDA coated on NiSe was 7.6% (Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“… Ye et al (2019) used a two-step method of splenization and electrochemical deposition to grow a cotton-like nickel sulfide material layer ( Figure 17 ) on nickel selenide nanorods, and obtained higher specific capacitance characteristics than general nickel selenide electrode materials. The SC obtained by assembling this electrode material and activated carbon reaches an energy density of 38.7 Wh/kg at a power density of 192 W/kg and still retains 85.9% of the initial value after 10,000 cycles.…”
Section: Materials Modificationmentioning
confidence: 99%